Study of the relationship between prolactin and TSH in infertile women in obari region in southern Libya - Maryam M. Bisher , Kalthom AL-zigny (Journal of Pure & Applied Sciences, 2019)
Infertility is the inability to have children after one year of marriage without using any contraceptive methods. The causes of infertility include thyroid disorders and high prolactin, so this study was conducted to investigate the relationship between thyroid disorders and prolactin in infertile women. The study included 80 women from the Ubari region between the ages of 20-39 year, 50 infertile women, 30 fertile women used as a control group. TSH and PRL were assayed using the immunoassay method on I Chroma instrument, in addition to calculating BMI for both groups, Analysis of variance and Pearson’s correlation were used to analyze the data, with the significant p-level set at 0.05. The results showed that the mean values of prolactin and TSH of the infertile women were significantly higher (p<0.05) than those of the controls. prolactin correlated positively and significantly with TSH in infertile women.This study concluded that thyroid disorders have an important effect on infertility in women through their effect on hormone Prolactin, so maintaining a normal concentration of thyroid hormones and prolactin is essential to maintaining good fertility among women.